Long Non-coding RNA KTN1-AS1 Targets miR-505 to Promote Glioblastoma Progression - Kai Guo; Lingling Fang; Mingjian Li; Aizheng Li; Na Liu (Behavioural Neurology)
Glioblastoma (GBM) is a highly malignant cancer, the prognosis of which is pretty poor. Long non-coding RNAs (lncRNAs) are a class of non-coding RNAs, which play important roles in carcinogenesis process of many cancers including GBM. In this study, we want to clarify the expression, biological function, and molecular mechanism of lncRNA KTN1 antisense RNA 1 (KTN1-AS1) in GBM tumor progression. We found that KTN1-AS1 expression was upregulated in GBM tissues and cell lines. KTN1-AS1 played oncogenic roles to facilitate proliferation, migration, and invasion of GBM cells. Then, we revealed that miR-505 was a target of KTN1-AS1, and its expression was decreased in GBM. KTN1-AS1 contributed to GBM progression by mediating miR-505. Finally, we demonstrated that KTN1-AS1 upregulated some target oncogenes of miR-505 including ZEB2, HMGB1, and RUNX2 in GBM cells. All in all, we concluded that the highly expressed KTN1-AS1 in GBM played oncogenic roles to facilitate GBM progression by targeting miR-505.